A CONSTRAINT BASED SYSTEM FOR LEXICAL KNOWLEDGE RETRIEVAL - Mihov, Stoyan (Ann. Sofia Univ. Fac. Math. and Inf., 1998)
This paper is concerned with the lexical knowledge retrieval system created at the Linguistic Modelling Laboratory. The main goal of the system is to provide a powerful and comfortable interface for lexical knowledge retrieval from large morphological dictionary. To achieve this a constraint based approach is applied that leads to a very effective algorithm. The algorithm for query building, which is also used for retrieving of general grammatical knowledge, is presented in details. In our opinion this method is very suitable for knowledge retrieval in domains with complex and irregular classifications.